2011
DOI: 10.1007/s00167-011-1781-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of femoral graft bending angle and tunnel length between transtibial technique and transportal technique in anterior cruciate ligament reconstruction

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
74
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 38 publications
(83 reference statements)
6
74
0
Order By: Relevance
“…Several studies report that the transportal technique for ACL reconstruction has a risk of short femoral tunnel length [13][14][15][16]. Miller et al [16] and Chang et al [15] reported that femoral tunnel length following the transportal technique was shorter than that using the transtibial technique, which is consistent with the results of our study (40.7 mm and 34.7 mm in transtibial and transportal groups, respectively).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Several studies report that the transportal technique for ACL reconstruction has a risk of short femoral tunnel length [13][14][15][16]. Miller et al [16] and Chang et al [15] reported that femoral tunnel length following the transportal technique was shorter than that using the transtibial technique, which is consistent with the results of our study (40.7 mm and 34.7 mm in transtibial and transportal groups, respectively).…”
Section: Discussionsupporting
confidence: 90%
“…Nishimoto et al [21] reported that the mean anteromedial (AM) femoral-graft bending angle was more acute than the mean posterolateral (PL) femoral-graft bending angle in double-bundle ACL with the transportal technique. Wang et al [13] reported that AM and PL femoral-graft angles in double-bundle ACL reconstruction using the transportal technique were more acute than single-bundle ACL reconstruction using the transtibial technique. As far as we are aware, this is the only study comparing graft bending angles at flexion and extension in single-bundle ACL reconstruction between transtibial and transportal techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outsidein (OI) and trans-tibial (TT) models created at 90° were matched to 0° and 130° models. Trans-portal (TP) models created at 130° were matched to 0° and 90° models consistent with our results [57]. There was a tendency that TT technique would reduce the bending angle for AM and singlebundle grafts, although it was still as high as 70° and GBA of PL-bundle in TT technique was even higher in our series.…”
Section: Discussionsupporting
confidence: 87%
“…Some previous studies have analyzed the femoral graft bending angle between femoral tunnel axis and graft at the femoral tunnel aperture in ACL reconstruction [12,16,18,23,26,27]. However, the relationship between femoral tunnel location and femoral graft bending angle has been little investigated.…”
Section: Introductionmentioning
confidence: 99%